Ear, nose, throat foreign bodies: experience in the tribal population - Gawarle, Surendra H.; Jondhale, Manoj; Keche, Prashant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Foreign bodies (FB) in the ears, nose or throat are a common occurrence in otorhinolaryngology (ENT) emergency services. The management calls for prompt & precise intervention which in turn decreases the overall morbidity and mortality. The aim of the study was to study the age & gender distribution, modes of presentation, management & complications of various foreign bodies in patients attending emergency & ENT OPD. Methods: It is a prospective, interventional clinical study conducted in a tertiary Care Hospital – Shri Vasantrao Naik government medical college situated in tribal region of Yavatmal, Maharashtra. About 200 patients from the tribal population with foreign body in ear, nose & throat region from November 2012 to October 2014 were included in the study. Results: Out of 200 patients, the commonest location of FB was in ear with 103 patients (51.5%) followed by nose with 72 patients (36%) and throat 25 patients (12.5%). 203 FB were removed from 200 patients. Throat cases include digestive tract (21 cases) and tracheobronchial (4 cases) FB. Amongst the FB in throat the commonest was fish bone and the commonest site being cricopharynx. Seeds were the commonest FB in ear & nose. A greater proportion of cases - 109 (54.5%) were below 10 years of age. Conclusions: A great degree of suspicion, prompt diagnosis and timely intervention can reduce the overall mortality and morbidity associated with ear, nose and throat foreign bodies.